PENGELOLAAN PEMBELAJARAN SIKAP DEMOKRATIS DI SMP MUHAMMADIYAH 1 KARTASURA - Nur Chayati; Eko Supriyanto; Muhammad Yahya (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
The purpose of this study were to determine: 1) Democratic values that the students developed in junior high school Muhammadiyah 1 of Kartasura students; 2) Learning strategy of democratic attitude in junior high school Muhammadiyah 1 of Kartasura; 3) Factors to be an obstacle in the learning of democratic attitudes in junior high school Muhammadiyah 1 of Kartasura.The study was conducted in junior high school Muhammadiyah 1 of Kartasura, with the kind of qualitative research. Data obtained by the method of interviewing, observation methods, and documentation. Data analysis methods used in this study is an interactive data analysis by using three main components, namely data reduction, presentation of data and drawing conclusions and also verification. While the data used to test the validity of the triangulation method.From interviews combined with observation and documentation of results, obtained results that: 1) The attitude of the developed democracies are attitudes based on values of openness, equality and the value of cooperation based on mutual respect; 2) Learning strategy of democratic attitude implemented by creating a democratic learning situation, get creative and open thinking and courage found. Implementation of learning strategies in developing the values of openness, equality and the value of cooperation through contextual learning strategies, inquiry and cooperative learning strategies. Evaluations democratic attitude of learning carried out after the learning process by looking at changes in behavior illustrates the extent to which the values that have been developed can be accepted and applied by the students. Evaluation conducted by the guidance counselor and teacher of all subjects, with an intensive observation and through direct inquiries to the responses of students on a case. Assessment results in the form of presentation in the form of quantitative assessment (score or number) and a qualitative assessment of verbal statements that are descriptive; 3) constraint in democratic attitude of learning is the unpreparedness of principals and teachers in implementing the changes to learning in developing democratic values, there is limited infrastructure and also lack of family support and people to introduce democratic values.